The Development of an Ethnopedagogical LMS to Enhance the Creativity of Elementary School Teacher Candidates in Learning Science Course - Muhammad Erfan; Ni Made Yeni Suranti; Ibrahim Ibrahim (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop an ethnopedagogy-based LMS tool to increase the creativity of prospective teacher students. This research is included in development research that adopts the 4D model. In this research, an ethnopedagogy-based LMS tool was produced that is oriented towards the creativity of prospective elementary school teachers. The tools developed are semester learning plans, student assignment plans, teaching materials, student worksheets, and creativity test instruments. The learning tools developed are integrated into the LMS so that users can access them online. The validity testing stage of the device was carried out by three experts. The validation test results were then analyzed using Aiken's V to determine the validity index of the content of the device being developed. Based on the results of data analysis, it can be concluded that the device developed is valid for use. Ethnopedagogy-based LMS tools can be used to train the creativity of prospective teacher students in elementary school science learning.